Key themes and research opportunities in sustainable supply chain management - identification and evaluation - Reefke, Hendrik; Sundaram, David (Elsevier, 2016)
Supply chains play an integral role in today's globalised economy. Hence, in order to truly pursue sustainable business development, the underlying dynamics and influential themes for sustainability in supply chains have to be understood. However, this area remains characterized by limited theoretical knowledge and practical application. A literature review was conducted first in order to gain an overview of available theory and to develop initial categorisations. In the next step, the insights of supply chain and sustainability experts were gathered via an exploratory Delphi study conducted online over three rounds. A set of key themes (planning, execution, coordination, and collaboration) and associated research opportunities (within the categories of governance, risk, compliance, performance management, and the sustainability dimensions) were synthesised and evaluated according to their relative importance based on the experts' opinions. By relating these results to existing literature, this study confirms, questions and extends knowledge on sustainable supply chain management. The identified themes are integral for the management and performance of sustainable supply chains. They provide structure to the field and offer a prioritisation of sustainability initiatives that can be applied prescriptively by the practitioner. The future research opportunities are further enfolded in a categorised research agenda, driving the theoretical as well as practical development of the field.
Keywords: Supply Chain Management; Sustainability; Delphi; Future Research; Risk; Performance